Genome-Wide Identification of Antimicrobial Intrinsic Resistance Determinants in Staphylococcus aureus - Vestergaard, Martin; Leng, Bingfeng; Haaber, Jakob; Bojer, Martin S.; Vegge, Christina S.; Ingmer, Hanne (Frontiers in Microbiology, 2016)
The emergence of antimicrobial resistance severely threatens our ability to treat bacterial infections. While acquired resistance has received considerable attention, relatively little is known of intrinsic resistance that allows bacteria to naturally withstand antimicrobials. Gene products that confer intrinsic resistance to antimicrobial agents may be explored for alternative antimicrobial therapies, by potentiating the efficacy of existing antimicrobials. In this study, we identified the intrinsic resistome to a broad spectrum of antimicrobials in the human pathogen, Staphylococcus aureus. We screened the Nebraska Transposon Mutant Library of 1920 single-gene inactivations in S. aureus strain JE2, for increased susceptibility to the anti-staphylococcal antimicrobials (ciprofloxacin, oxacillin, linezolid, fosfomycin, daptomycin, mupirocin, vancomycin and gentamicin). 68 mutants were confirmed by E-test to display at least two-fold increased susceptibility to one or more antimicrobial agents. The majority of the identified genes have not previously been associated with antimicrobial susceptibility in S. aureus. For example, inactivation of genes encoding for subunits of the ATP synthase, atpA, atpB, atpG and atpH, reduced the minimum inhibitory concentration (MIC) of gentamicin 16-fold. To elucidate the potential of the screen, we examined treatment efficacy in the Galleria mellonella infection model. Gentamicin efficacy was significantly improved, when treating larvae infected with the atpA mutant compared to wild type cells with gentamicin at a clinically relevant concentration. Our results demonstrate that many gene products contribute to the intrinsic antimicrobial resistance of S. aureus. Knowledge of these intrinsic resistance determinants provides alternative targets for compounds that may potentiate the efficacy of existing antimicrobial agents against this important pathogen.